Performance of green and conventional techniques for the optimal extraction of bioactive compounds in bee pollen - Aylanc, Volkan (2022)
The exploitation of phenolic compounds in different fields has motivated researchers to explore eco-friendly and efficient extraction techniques. This study aimed to comparatively reveal that green extraction techniques (microwave- and ultrasound-assisted) are alternative to conventional extraction (maceration and magnetic stirring) with positive impact on the phenolic content, antioxidant activity, and bioactive profile of bee pollen extracts. The highest total phenolic and flavonoid content was reached using the microwave-assisted technique (MAE) with equivalent values of 28 and 8 mg g−1, with magnetic stirring and maceration showing a lower value. The composition profile of the extracts revealed the presence of twenty-six bioactive compounds, including thirteen phenolics and thirteen phenylamides. Although the extraction technique had little impact on the chemical diversity, the amount of bioactive compounds raised significantly with the use of the green extraction techniques, with gains between 40% and 60% for phenolics and up to 200% for phenylamides. The radical scavenging activity and the reducing power of the extracts confirmed that bee pollens are potent antioxidant source, with the most bioactive extracts corresponding to green extraction techniques. Consequently, all findings recommend the use of MAE as the technique most effective for the extraction of bioactive compounds from naturally encapsulated structures such as bee pollen.